Perancangan Rebranding Untuk Meningkatkan Brand Awarness Rumah Kue Wiweka Sebagai Toko Oleh-Oleh Khas Batam - Maheswari, Made Ruby Candra; Setiawan, Bayu; Wulandari, Sri (STIE AMKOP, 2025)
The culinary sector is growing rapidly in Batam because tourists are willing to pay high prices for local specialties. This has led to the emergence of many food and souvenir shops in Batam. Therefore, a unique brand identity is needed. One of Batam's specialty souvenir shops, Rumah Kue Wiweka, has a vision of becoming the primary choice for tourists. However, Rumah Kue Wiweka has a weak brand identity, making it difficult for tourists to recognize it. A rebranding design is a possible solution so that Rumah Kue Wiweka can strengthen its brand identity as the number one choice souvenir shop in Batam. This design uses qualitative research methods that prioritize interviews, literature studies, and customer journey analysis. Several concepts generated from the data analysis will later serve as references in the rebranding design: verbal concepts, visual concepts, and media concepts. Thus, this design is expected to be a solution for Rumah Kue Wiweka to increase brand awareness as a specialty souvenir shop in Batam.